Analisis penerapan e-faktur pajak oleh pengusaha kena pajak di KPP Pratama Manado - Repi, Imiko Elissa; Elim, Inggriani; Wangkar, Anneke (Yayasan Widyantara Nawasena Raharja, 2025)
The Indonesian tax reform has made significant changes to the tax administration system, including replacing paper tax invoices with electronic invoices (e-Invoices).This research analyses the implementation of Tax e-Invoices by Taxable Entrepreneurs in reporting their Value Added Tax (VAT) Periodic Tax Returns at KPP Pratama Manado.The research method used is a qualitative descriptive case study approach. The results of the research at KPP Pratama Manado show that the implementation of e-invoices has been successful, making it easier for KPP Pratama and Taxable Entrepreneurs. There are still some obstacles, such as network constraints and some Taxable Entrepreneurs' lack of understanding, but these can be overcome by KPP Pratama Manado. The use of e-invoices in reporting the current VAT period is effective in improving Taxable Entrepreneurs' compliance, as shown by the year-on-year compliance rate. In 2022, the rate was 91.86%, and in 2023, it was 92.92%.